Gamelan Soepra: Konsep dan Perilaku Musikal untuk Mencapai Tujuan Pendidikan - Agustinus Sani Aryanto (Institut Seni Indonesia Denpasar, 2018)
Soepra Gamelan is a set of gamelan adapted from Javanese Gamelan and has diatonic note like westen musical instruments. Soepra Gamelan is played with combo band and string section. Soepra Gamelan was created by a Jesuit from Netherlands Henricus Constant Van Deinse SJ in 1957. Soepra Gamelan has become a music subject in Loyola Senior High School Semarang since 2011. This research is to know the essence of Soepra Gamelan as a music learning means and to describe concept, musical behaviour, and the sound of Soepra Gamelan in Loyola Junior High School Semarang. Method in this research is qualitative using observation, interview, and literature study. This research is based on musicology approach. The approach is used to analyze instrumentalitation in Soepra Gamelan. The data is analyzed by using Musical Activity Theory by Alan P Merriam regarding the concept, musical behaviour, and the sound of Soepra Gamelan while Herbert Read theory is used to analyze the function of learning as a musical educational means in Loyola Senior High School Semarang. The result of this research is that Loyola Senior High School Semarang has a special method in introducing gamelan. Musical scale in Soepra Gamelan has an advantages and disadvantages (positive and negative impacts). Students can play many genre of songs in pentatonic and diatonic musical scale easily but, however, the characters of Javanese musical scale are disappeared. Through Soepra Gamelan, the students can recognize western and eastern culture from musical instrument and repertoire songs. Routine concert in performing the gamelan gives a real experience to the students in terms of process, preparation, and performance.